Type A personality and mortality: Competitiveness but not speed is associated with increased risk. (July 2017) - Lohse, Tina; Rohrmann, Sabine; Richard, Aline; Bopp, Matthias; Faeh, David; ,
Abstract: Background and aims: Type A behavior pattern (TABP) is a possible risk factor for cardiovascular disease (CVD). However, existing evidence is conflicting, also because studies did not examine underlying traits separately. In this study, we investigated whether all-cause and CVD mortality were associated with the Bortner Scale, a measure of TABP, in particular with its subscales competitiveness and speed. Methods: Information on Bortner Scale and covariates of 9921 participants was collected at baseline in two cross-sectional studies that were linked with mortality information, yielding a follow-up of up to 37 years. We analyzed the Bortner Scale and its two subscales competitiveness and speed. Applying Cox regression models, we investigated the association with all-cause, CVD, and specific CVD type mortality. Results: During follow-up, 3469 deaths were observed (1118 CVD deaths). The total Bortner Scale was not associated with mortality, only its subscales. In women, competitiveness was positively associated with all-cause mortality (highest category vs. the lowest, HR 1.25 [95% CI 1.08, 1.44]), CVD mortality (1.39 [1.07, 1.81]), and ischemic heart disease mortality (intermediate category vs. the lowest, 1.46 [1.02, 2.10]). In men, CVD mortality was inversely associated with speed (highest category vs. the lowest, 0.74 [0.59, 0.93]). Conclusions: The subscales of the Bortner Scale may be associated with CVD in an opposed manner and may therefore have to be analyzed separately. More studies are needed to further investigate this association, also considering differences by sex. Persons scoring high in the competitiveness subscale ought to be screened and counselled in order to reduce their CVD risk. Highlights: The Bortner Scale (measuring type A personality) was not associated with mortality. Its subscales were associated with mortality in an opposed manner. In women, competitiveness was associated with increased CVD and IHD mortality. In men, speed was associated with reduced CVD mortality.